2017
DOI: 10.14710/jitaa.42.2.72-80
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenecity of H5N1 highly pathogenic Avian Influenza (HPAI) virus clade 2.3.2. in Indonesian indigenous chicken by contact tranmission with infected duck

Abstract: An experimental transmission study was conducted using nine healthy Indonesian indigenous chickens placed together with two 30 days old ducks which were experimentally infected with H5N1 HPAI clade 2.3.2 virus in the Biosafety Laboratory Level 3 (BSL-3) facilities. The aim of the study was to find out the pathogenicity of H5N1 HPAI virus clade 2.3.2 in Indonesian indigenous chickens. The study showed that within twenty four hours rearing, the chickens were exhibited mild clinical signs and by 48 hours, all of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…The results suggest that clade 2.3.2.1c of HPAI A(H5N1) is more virulent to ducks than the previously circulating clade 2.1.3. Our observations are in line with those observed in ducks after experimental inoculation of this virus clade [34], but the background for the difference in clinical manifestations of the two different subgroup of A(H5N1) clade 2.3.2.1c (A and B) is not clear yet. Previous pathobiological study of A(H5N1) infections showed different clinical manifestation of Indonesian A(H5N1) viruses representing clades 2.1.1 and 2.1.3 in ducks and chickens [35].…”
Section: Discussionsupporting
confidence: 91%
“…The results suggest that clade 2.3.2.1c of HPAI A(H5N1) is more virulent to ducks than the previously circulating clade 2.1.3. Our observations are in line with those observed in ducks after experimental inoculation of this virus clade [34], but the background for the difference in clinical manifestations of the two different subgroup of A(H5N1) clade 2.3.2.1c (A and B) is not clear yet. Previous pathobiological study of A(H5N1) infections showed different clinical manifestation of Indonesian A(H5N1) viruses representing clades 2.1.1 and 2.1.3 in ducks and chickens [35].…”
Section: Discussionsupporting
confidence: 91%
“…The highest prevalence and mortality were reported in backyard chickens (average 59%, range: 49-69%), compared to ducks (average 32%, range: 19-45%) and other birds (average 28%, range: 16-40%) (11,12). Another study conducted by R. Damayanti et al (39) to determine the effect and pathogenicity of AIV H5N1 HPAI virus found clade 2.3.2 in 30-day old infected ducks and indigenous chickens by rearing together. The results of the investigation revealed that all chickens have died after 48 hours, whereas ducks just displayed clinical indications (39).…”
Section: Effects Of Avian Influenza On Species Of Birdsmentioning
confidence: 96%
“…Another study conducted by R. Damayanti et al (39) to determine the effect and pathogenicity of AIV H5N1 HPAI virus found clade 2.3.2 in 30-day old infected ducks and indigenous chickens by rearing together. The results of the investigation revealed that all chickens have died after 48 hours, whereas ducks just displayed clinical indications (39). In comparison to ducks, chickens have a higher infection and incidence rate of AIV.…”
Section: Effects Of Avian Influenza On Species Of Birdsmentioning
confidence: 99%
“…Keberagaman jenis unggas yang dijual di pasar meningkatkan potensi penyebaran HPAI dari itk yang terinfeksi pada penelitian ini. Itik yang terinfeksi dapat menyebarkan virus kepada ayam dan unggas rentan lain secara efisien dengan tingkat kematian yang tinggi, karena ayam dan unggas lain memiliki kerentanan yang relatif lebih tinggi terhadap HPAI H5N1 dibandingkan dengan itik (Damayanti et al, 2017;Kang et al, 2017).…”
Section: Uji Reverse Transcriptase Polymerase Chain Reactionunclassified